Spring Dispersal of Northern Bobwhites in Southwestern Ohio - Marjorie R. Liberati; Robert J. Gates (National Quail Symposium Proceedings, 2017)
Northern bobwhites (Colinus virginianus) historically occurred throughout Ohio but their core range has contracted to 18 southwestern counties. The Ohio Division of Wildlife has used trapping and transplanting to reintroduce wild bobwhites to unoccupied habitats within the species’ historic range. Bobwhite dispersal information is necessary to understand population dynamics and the species’ capacity to recolonize unoccupied habitats. Bobwhites were captured and radiomarked on 4 private-land study sites in southwestern Ohio. Radio-marked bobwhites (n 1⁄4 66) were tracked by homing or triangulation during spring 2010 and 2011 to ascertain dispersal distances between winter and breeding ranges. The spring dispersal period was defined by break-up of coveys and subsequent occupation of breeding season home ranges. The dispersal period, defined by non-affiliation with coveys, long directional daily movements, and observed breeding activity, varied among individuals and ranged from 2 April to 26 May. Dispersal distances were measured as the net Euclidean distance between locations recorded at the beginning and end of the dispersal period. Dispersers were defined as birds that moved . 23 the diameter of the mean home-range size (26.1 ha) observed during October-March 2010 and 2011. Movements of 1–2 home-range diameters were classified as home range shifts. Non-dispersing bobwhites traveled , 1 home-range diameter. Mean movement for all birds was 1.54 km. Twenty-eight (42.4%) radio-marked bobwhites were non-dispersers, 15 (22.7%) shifted home ranges, and 23 (34.8%) dispersed. Non-dispersers moved a mean of 0.31 km (range 1⁄4 0.03–0.56 km), home range shifts averaged 0.78 km (range 1⁄4 0.60–0.99 km), and dispersers traveled a mean distance of 3.6 km (range 1⁄4 1.18–11.5 km). Dispersal distance was lowest for adult females and increased in order for adult males, juvenile females, and juvenile males. Dispersal distance decreased as the proportion of early successional wooded habitat within winter home ranges increased. Sex, age, and dispersal distance did not affect survival. Our results suggest Ohio bobwhites are capable of expanding their range into historically-populated areas.
Keywords: Northern bobwhite; Colinus virginianus; dispersal; early successional habitat; home range shift; Ohio